Development Flashcard to Teach Speaking Skill in Recount Text - Utami, Nurcholisa Rizqi; Rofi'ah, Siti; Makrifah, Istina Atul (IKIP Siliwangi, 2025)
This study aims to develop flashcards as learning media to teach students' English language skills. This study uses the Research and Development (R&D) method with the ADDIE model which consists of five stages namely analysis, design, development, implementation, and evaluation. Qualitative data was collected from classroom observations and validator feedback on the flashcards. Quantitative data was collected through questionnaires using a Likert scale for instrument validation, media, materials, and student satisfaction. The instrument validation received a percentage of 100% with the category “Very Valid”, the media validation received 66.66% with the category “Valid”, and the material validation was 92.85% with the category “Very Valid”. This study found an increase in students' speaking ability when using flashcards as learning media. This is evidenced by the pre-test and post-test which increased 9,38%. This finding shows that the flashcards developed are valid, feasible, and effective media for teaching and improving students' English speaking skills.